Meningkatkan kualitas proses pembelajaran melalui pelatihan pembelajaran matematika realistik - Alimuddin Alimuddin; Usman Mulbar; Nasrullah Nasrullah; Ahmad Zaki (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
PKM program was performed by providing trainingand mentoring activities to participants about the RealisticMathematics Education for elementary school teachers withthe aims of (1) to increase knowledge about the RealisticMathematics Eduaction, (2) participants can implement theRealistic Mathematics Education in the learning process, and(3) participants can disseminate or disseminate knowledge ofthe Realistic Mathematics Education. The main targetaudience of this PKM program were school supervisors,school principals and school teachers in the TinggimoncongDistrict, Gowa Regency, South-Sulawesi Province. The resultsobtained in the PKM program activities were increasedknowledge and concepts of Realistic Mathematics Educationof PKM program participants, increased development skills inthe Realistic Mathematics Education of PKM programparticipants, PKM program participants can make examplesand compile the Realistic Mathematics Education activities inthe class, and PKM program participants can implement theRealistic Mathematics Education in the learning process atschool. Other results obtained were increased of participants’motivation in knowing the material of realistic mathematicslearning and the high enthusiasm of participants indisseminating the results of PKM program, especially thematerial on Realistic Mathematics Education.